Patient Satisfaction with the Quality of Nursing Care in Public and Private Hospitals in Erbil City - Ali Taher Mohammedameen; Azzadin Kamal Mahmod; Yousif Bakr Omar; Haval Mohammed Qadir; Sideeq Sadir Ali; Burhan Ezzadin Sabir (Hawler Medical University, 2024)
Background and Objectives: Patient satisfaction is an essential parameter in assessing the quality of care and healthcare facility performance and the most important competitive advantage of the government and private hospitals. The study aims to investigate patients' satisfaction regarding the quality of nursing care in both public and private hospitals. Methods: A quantitative, comparative study was conducted among 330 patients (165 from public hospitals and 165 from private hospitals) in Erbil City from October 2023 to February 2024. Data were collected through structured interviews using a standardized questionnaire and analyzed using descriptive and inferential statistics via the Statistical Package for the Social Sciences. Results: Among the 330 patients surveyed, the majority were aged 18 to 39 years (55.8%), predominantly female (65.5%) and married (75.2%). Notably, 50.3% had been hospitalized over four times in public hospitals. Patients reported their health status as fair (38.8% before hospitalization), with 64.2% transferred from other facilities. In private hospitals, 100% of patients had single occupancy in their rooms. Satisfaction scores for nursing care were significantly higher in private hospitals compared to public ones (p < 0.001). Significant associations were observed between sociodemographic factors and nursing care satisfaction (p < 0.001), with gender showing no significant association (p = 0.819). Conclusions: The study concludes that patients in private hospitals exhibit strong satisfaction with the quality of nursing care compared to those in public hospitals. This highlights the importance of addressing disparities in nursing care quality between hospital types to enhance overall patient satisfaction and healthcare outcomes.